Effect of hydrothermal treatment on physical and semolina milling properties of barley. (December 2020) - Karanam, Muralidhar; Theertha, D.P.; Kumar, Ashwin; Inamdar, Aashitosh A.; Sakhare, Suresh D.
Abstract: Barley samples were treated hydrothermally (HTT) to modify their physical properties for the production of semolina. HTT has increased the hardness value and firming of the barley structure with more compactly packed starch in the protein matrix of grain with increase in treatment time. Treated barley samples were milled in laboratory roller mill which resulted in the production of four fractions namely husk (HK), coarse semolina (CS), fine semolina (FS) and flour (FL). Total semolina yield increased up to 20 min of steaming to 86.69% but decreased on further time increase. Barley pretreatment was found to be necessary to obtain increased yield and uniform sized firm semolina granules. Water holding capacity of semolina significantly increased (232 g/100 gm) with increase in the HTT time. The solubility index of semolina decreased (3.56%) with increase in the HTT time. Pasting temperature of semolina increased while viscosity decreased with increase an HTT time. Highlights: Barley was treated hydrothermally for the production of semolina. Pre-treatment increased the hardness of grain with increase in treatment time. Pre-treatment of grains significantly increased yield and quality of semolina. Pasting temperature increased while viscosity decreased with increase an HTT time. Roller milling proved to be a potential method for production of barley semolina.